Workshop Penggunaan Media Pembelajaran Berbasis Sampah dan Barang Bekas Bagi Guru MIN TTU - Hermina Disnawati; Farly Oktriany Haning (Bakti Cendana, 2019)
The main problems in primary school of MIN TTU-Kefamenanu were: (i) the unavailability of mathematics manipulatives for helping teacher and students learn meaningfully; (ii) there has never been a workshop about mathematics manipulatives. The method that used in this workshop : lectures, demonstration, direct practices, discussion, and assignment. The manipulatives that are used are Numeral Ruler, Positives-Negatives Cards, LCM and GCF Puzzle, Magic Square, Canadian Multiplication, Congklak , Cayley Tables, Math Snake-Ladders Game, Hanoi Tower and Tangram. All of these manipulatives were made from garbage and used goods. The workshop held in 3 days which was the first day focus on teachers and the next two days was focus on practice of using manipulatives which involved students grade 4th, 5th and 6th. The results from questionnaire showed that i) 33.33% of participants strongly agreed and 66.67% of workshop participants agreed that the workshop material was well organized and the workshop content appropriate with curriculum in elementary schools, the manipulatives was interesting for students and helping them to learn while playing; ii) 80% of participants agreed and 20% strongly agreed that the practice guidelines with worksheets was well understood.